POEML: a Process Orchestration, Execution, and Modeling Language. Issue 6 (24th April 2022) - Hachemi, Asma; Ahmed‐Nacer, Mohamed
Abstract: Many software process modeling languages are available today, but the majority do not meet the community's expectations. They are complex, difficult for enactment, and so forth. After studying the state of the art, we asked this research question: Is it possible to have an easy to read and use Software Process Modeling Language (SPML), which is abstract enough but also expressive enough to suit different domains of process modeling and allowing the orchestration and execution of the process models it expressed? Our contribution consists in answering this question by defining Process Orchestration, Execution and Modeling Language (POEML), an SPML that supports the static process modeling and also the dynamic aspects of orchestration and execution. This language is governed by a metamodel, according to MDE principles, and provides graphic notation and a support tool. Its demonstration involves a benchmark that assesses the applicability of the language. We evaluate our language through a set of SPMLs quality criteria. Our contribution is discussed in terms of adopted choices and is compared with different related works. POEML contributes to software processes practice by linking modelization to execution while compensating some gaps still posed in SPMLs, which is an important improvement in this field. Abstract : Process Orchestration, Execution and Modeling Language (POEML) is an abstract enough but also expressive enough Software Process Modeling Language (SPML) that suits different domains of process modeling and that allows the orchestration and execution of the process models it expressed. It is governed by a metamodel and provides graphic notation and a support tool. POEML contributes to software processes practice by linking modelization to execution while compensating some gaps still posed in SPMLs.